A SIMPLE MODEL FOR THE CHLORIDE DIFFUSION COEFFICIENT OF STEEL FIBRE REINFORCED CONCRETE - Mwila Chitakwa; Qiannan Wang; Peng Yuxiang; Gao Zesu; Zhang Weibin; Yang Lixia; Gu Chunping (Ceramics-Silikáty, 2021)

(untitled)
The chloride diffusion coefficient is the most important parameter when describing the chloride ingress in concrete. This paper proposes a simple model to predict the chloride diffusion coefficient of steel fibre reinforced concrete (SFRC). The chloride diffusion coefficients of a cement paste and an interfacial transition zone (ITZ) were calculated with their porosities, respectively. The ITZ porosity was obtained with a w/b ratio based on a porosity model. The chloride diffusion coefficient of the matrix was then determined according to the general self-consistent scheme, and the influence of the steel fibre was simplified with its volume fraction. The calculated chloride diffusion coefficient of the SFRC was verified with the results from the bulk diffusion tests and the accuracy was acceptable.